MODULE DEVELOPMENT WITH MIND MAP NUANCES THE PRACTICAL SYSTEM OF REGULATION HUMAN FOR CLASS XI SCIENCE STUDENTS SENIOR HIGH SCHOOL - Itgo Hatchi; Januardi Rosyidi Lubis; Mutia Nasution (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
Biology is one of the subjects related to nature. Not all material can be immediately understood by students. Students need media in learning such as modules. The fact is that at SMA Negeri 1 Gunung Talang, Solok Regency, in class XI IPA 1 there are still students whose grades are below the KKM on the human regulatory system material. This is because students do not have interesting learning resources. Based on this, research was carried out with the aim of developing mind map-based learning modules on practical human regulatory systems. This learning methodology module was developed using the 4-D model, namely define, design, and develop, while the disseminate stage was not carried out. Data collection was carried out by validating and testing the developed learning modules. The module design that has been designed, validated by experts and practitioners, is then tested on a limited basis in class XI IPA 1 SMA Negeri 1 Gunung Talang to find out the practicality of the learning module. Based on the results of the module practicality test by the teacher, it has very practical criteria with a score of 88,69%. The practicality test of learning modules by students has very practical criteria with a score of 89,38%. Thus, it can be concluded that the mind map-based module on human regulatory system material for class XI IPA of senior high schools is declared practical.